Policy Network Model In Tourism Development And Growth In Bandung - Ine Mariane; Mona Indrianie; Dayang rekha septula; Shenyhadi Apriliany (International Journal of Economics, Business and Innovation Research, 2024)
This study examines the implementation of policy networks in tourism development and expansion in Bandung City, Indonesia. It addresses the diverse potentials, challenges, and impacts of tourism, focusing on relationships among actors within a good governance framework. Using a qualitative approach with literature study and phenomenology methods, the research investigates policy networks across economic, environmental, social, and cultural sectors. Findings indicate that tourism development prioritizes cultural preservation, historical heritage, and product diversification. The research concludes that synergy between government, entrepreneurs, and community is crucial for effective tourism development. This study contributes to the understanding of policy networks in urban tourism development, offering insights for policymakers and stakeholders in similar contexts.